Estrogenic-Like Potential of Aqueous Extract of Soursop and Johar Leaf Extract (Annona muricata) on MCF-7 and NIH-3T3 Cells - Umaru, Isaac John; Tiimob, Gideon Likida; Yahaya, Musbau Adekunle; Oteng, Joseph (Darul Yasin Al Sys, 2026)
Annona muricata (soursop) is a tropical plant widely recognized for its pharmacological properties, including anticancer, anti-inflammatory, and hormonal regulatory effects. This study examines the estrogenic-like potential of aqueous leaf extracts of A. muricata and Siamese senna (Johar) on estrogen receptor-positive human breast adenocarcinoma cells (MCF-7). A series of in vitro assays—including cell viability analysis, morphological assessment, and estrogen receptor expression profiling—were conducted to evaluate the bioactivity of the extracts. Results indicate that the A. muricata extract exerts a dose-dependent proliferative effect on MCF-7 cells, consistent with estrogenic activity. These findings suggest that A. muricata may act as a phytoestrogen, with potential applications in hormone-related therapeutic interventions. Further research is recommended to elucidate the molecular mechanisms underlying its estrogenic effects and to assess its safety and efficacy in vivo, particularly in the context of hormone-sensitive cancers.